Catalyst coating proton membrane and preparation method thereof, membrane electrode and fuel cell

By forming two catalytic layers on the proton exchange membrane of the fuel cell, and using ionomer resin as the second catalytic layer, the problem of large interface impedance between the catalytic layer and the proton exchange membrane is solved, and the electrochemical performance of the membrane electrode is improved.

CN119650719APending Publication Date: 2025-03-18CHINA AUTOMOTIVE INNOVATION CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411894683.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the existing fuel cell catalyst-coated proton membrane, the interface impedance between the catalytic layer and the proton exchange membrane is relatively large, affecting the electrochemical performance.

Method used

Using the structure of two catalytic layers, a first catalytic layer and a second catalytic layer are formed on the proton exchange membrane. The second catalytic layer is composed of ionomer resin, and the two catalytic layers are transferred to the proton exchange membrane through a transfer process.

Benefits of technology

The compatibility between the catalytic layer and the surface of the proton exchange membrane is improved, the interface impedance is reduced, and the proton conduction efficiency is improved, thereby improving the electrochemical performance of the membrane electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650719A_ABST
    Figure CN119650719A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst coating proton membrane and a preparation method thereof, a membrane electrode and a fuel cell, and the method comprises the following steps: providing a transfer printing substrate and a proton exchange membrane, and forming a first catalyst layer comprising ionomer resin and a catalyst on the transfer printing substrate; forming a second catalytic layer comprising an ionomer resin on the first catalytic layer; and transferring the first catalyst layer and the second catalyst layer on the transfer substrate to the proton exchange membrane through a transfer process, so that the second catalyst layer is positioned on the proton exchange membrane and the first catalyst layer is positioned on the second catalyst layer, thereby obtaining the catalyst coating proton membrane. The two catalyst layers are arranged, the second catalyst layer is additionally arranged between the first catalyst layer and the proton exchange membrane, and the second catalyst layer is the ionomer resin layer, so that the compatibility between the second catalyst layer and the surface of the proton exchange membrane is improved, and the interface impedance between the second catalyst layer and the proton exchange membrane is reduced; and the proton conduction efficiency of the catalyst coating proton membrane is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells, and in particular to a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell. Background Art

[0002] As a new generation of new energy, fuel cells are an efficient, environmentally friendly and sustainable energy source, and they play an indispensable role in achieving carbon peak and carbon neutrality in the future. The catalyst-coated proton membrane of the fuel cell includes a proton exchange membrane and a catalytic layer. The catalyst-coated proton membrane prepared by the current transfer printing process has a large interface impedance between the catalytic layer and the proton exchange membrane. Summary of the invention

[0003] In view of the above problems, the object of the present invention is to provide a catalyst-coated proton membrane capable of reducing the interface impedance between the catalyst layer and the proton exchange membrane, a preparation method thereof, a membrane electrode and a fuel cell. The technical solution is as follows:

[0004] In one aspect, a method for preparing a catalyst-coated proton membrane is provided, the method comprising:

[0005] Providing transfer matrix and proton exchange membrane;

[0006] forming a first catalyst layer on the transfer substrate; the first catalyst layer comprises an ionomer resin and a catalyst;

[0007] forming a second catalytic layer on the first catalytic layer; the second catalytic layer comprises an ionomer resin;

[0008] The first catalytic layer and the second catalytic layer on the transfer substrate are transferred to the proton exchange membrane through a transfer process, so that the second catalytic layer is located on the proton exchange membrane and the first catalytic layer is located on the second catalytic layer, thereby obtaining a catalyst-coated proton membrane.

[0009] In an exemplary embodiment, the process conditions of the transfer process include:

[0010] The temperature is 120-170°C;

[0011] The transfer pressure is 2-2.5Mpa;

[0012] The transfer time is 2 to 3 minutes.

[0013] In an exemplary embodiment, forming a first catalytic layer on the transfer substrate comprises:

[0014] Providing a first material; the first material comprises a first solid material and a first solvent; the first solid material comprises an ionomer resin and a catalyst;

[0015] Applying the first material on the transfer substrate to form a first catalytic layer on the transfer substrate;

[0016] The forming of a second catalytic layer on the first catalytic layer comprises:

[0017] Providing a second material; the second material comprises a second solid material and a second solvent; the second solid material comprises an ionomer resin;

[0018] The second material is applied on the first catalytic layer to form a second catalytic layer on the first catalytic layer.

[0019] In an exemplary embodiment, the second catalytic layer further comprises a catalyst;

[0020] The second material further comprises a catalyst; and the content of the ionomer resin in the second solid material is greater than the content of the ionomer resin in the first solid material.

[0021] In an exemplary embodiment, the second catalytic layer further comprises a carbon material;

[0022] The second material also includes the carbon material;

[0023] The carbon material includes one or more combinations of carbon nanotubes, carbon fibers, and graphene.

[0024] In an exemplary embodiment, the solid content of the second material is lower than the solid content of the first material; the solid content represents the mass percentage of the solid material in the material;

[0025] The solid content of the second material is 1% to 25%;

[0026] The thickness of the second catalytic layer is smaller than the thickness of the first catalytic layer.

[0027] In an exemplary embodiment, the second solvent includes water and an organic solvent; the mass ratio of the water to the organic solvent is 0.1-10.

[0028] On the other hand, the present invention also provides a catalyst-coated proton membrane, including any catalyst-coated proton membrane prepared by any of the above-mentioned preparation methods.

[0029] On the other hand, the present invention also provides a membrane electrode, comprising any one of the above-mentioned catalyst-coated proton membranes.

[0030] On the other hand, the present invention also provides a fuel cell, comprising the above-mentioned membrane electrode.

[0031] The invention discloses a method for preparing a catalyst-coated proton membrane, providing a transfer substrate and a proton exchange membrane, forming a first catalyst layer including an ionomer resin and a catalyst on the transfer substrate; forming a second catalyst layer including an ionomer resin on the first catalyst layer; transferring the first catalyst layer and the second catalyst layer on the transfer substrate to the proton exchange membrane through a transfer process, so that the second catalyst layer is located on the proton exchange membrane and the first catalyst layer is located on the second catalyst layer, thereby obtaining a catalyst-coated proton membrane. The invention provides two catalyst layers, and adds a second catalyst layer between the first catalyst layer and the proton exchange membrane, wherein the second catalyst layer is an ionomer resin layer, thereby improving the compatibility of the second catalyst layer with the surface of the proton exchange membrane, reducing the interface impedance between the second catalyst layer and the proton exchange membrane, and improving the proton conduction efficiency of the catalyst-coated proton membrane, thereby improving the performance of the membrane electrode based on the catalyst-coated proton membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 It is a flow chart of a method for preparing a catalyst-coated proton membrane provided by an embodiment of the present invention;

[0034] Figure 2 It is a comparison diagram of polarization curves of voltage and resistance of different membrane electrodes provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] As a new generation of new energy, hydrogen fuel cells are an efficient, environmentally friendly and sustainable energy source. They play an indispensable role in achieving carbon peak and carbon neutrality in the future. The construction of the three-phase interface of the catalyst layer is essentially to achieve the regulation and distribution of key parameters such as mass transfer, drainage, and conductivity at the interface, including the interface characteristics between the bipolar plate and carbon paper, carbon paper and catalyst layer, and catalyst layer and proton exchange membrane. In particular, reducing the interface resistance between the catalyst layer and the proton exchange membrane is the core direction of reducing the ohmic impedance of the membrane electrode. In addition, transfer printing is a common catalyst coated proton membrane (CCM) preparation scheme in the mass production of membrane electrodes. The transfer process has always had a large interface resistance between the catalyst layer and the proton membrane, which affects the electrochemical performance of the membrane electrode; in addition, the transfer process also faces process problems such as high transfer operating temperature and high pressure.

[0037] Therefore, it is very necessary to develop a new catalyst-coated proton membrane preparation method to reduce the interfacial impedance between the catalyst layer and the proton exchange membrane.

[0038] The present application provides a method for preparing a catalyst coating proton membrane. Figure 1 , Figure 1 The present invention is a flow chart of a method for preparing a catalyst-coated proton membrane, wherein the method comprises the following steps:

[0039] Step S1: providing a transfer matrix and a proton exchange membrane.

[0040] Step S2: forming a first catalyst layer on the transfer substrate; the first catalyst layer comprises an ionomer resin and a catalyst.

[0041] Specifically, the present invention does not impose any specific limitation on the types of the ionomer resin and the catalyst in the first catalyst layer.

[0042] Step S3: forming a second catalytic layer on the first catalytic layer; the second catalytic layer comprises an ionomer resin.

[0043] Specifically, when selecting the type of ionomer resin for the second catalytic layer, it is best to keep it consistent with the type of ionomer resin on the proton exchange membrane, or the two types are close to each other, so as to ensure the surface compatibility of the second catalytic layer and the proton exchange membrane and reduce the interface impedance between the second catalytic layer and the proton exchange membrane.

[0044] Step S4: Transferring the first catalytic layer and the second catalytic layer on the transfer substrate to the proton exchange membrane through a transfer process, so that the second catalytic layer is located on the proton exchange membrane and the first catalytic layer is located on the second catalytic layer, to obtain a catalyst-coated proton membrane.

[0045] In the embodiment of the present application, the process conditions of the transfer process include:

[0046] The temperature is 120-170°C;

[0047] The transfer pressure is 2-2.5Mpa;

[0048] The transfer time is 2 to 3 minutes.

[0049] Specifically, the present application takes into account that the glass transition temperature of the proton exchange membrane is between 120 and 130°C. When the temperature is higher than 150°C, the microstructure of the proton membrane is prone to segment movement and rearrangement, thereby affecting proton conduction. In the embodiment of the present application, a second catalyst layer with an ionomer resin as the main component is added, and the content of the ionomer resin in the second catalyst layer is greater than the content of the ionomer resin in the first catalyst layer, so that the second catalyst layer has a higher compatibility with the surface of the proton exchange membrane, and can also reduce the process conditions of the transfer process, especially the transfer pressure. The transfer can be completed at a temperature of 120 to 170°C, a transfer pressure of 2 to 2.5 MPa, and a transfer time of 2 to 3 minutes, which reduces the difficulty of the transfer process, and the microstructure of the obtained catalyst coating proton membrane is not prone to segment movement and rearrangement. The standard for completion of the transfer is complete transfer, and there is no residue on the transfer matrix.

[0050] In the embodiment of the present application, forming a first catalyst layer on the transfer substrate includes:

[0051] Providing a first material; the first material comprises a first solid material and a first solvent; the first solid material comprises an ionomer resin and a catalyst;

[0052] Applying a first material on the transfer substrate to form a first catalytic layer on the transfer substrate;

[0053] Forming a second catalytic layer on the first catalytic layer includes:

[0054] Providing a second material; the second material comprises a second solid material and a second solvent; the second solid material comprises an ionomer resin;

[0055] The second material is applied on the first catalytic layer to form a second catalytic layer on the first catalytic layer.

[0056] Specifically, a first material is provided and a conventional coating method is used to form a first catalytic layer on the transfer substrate, and the coating method includes slit coating, scraper coating, spraying and other process methods; illustratively, a second material is provided and a spraying method is used to form a second catalytic layer on the first catalytic layer, and the thickness of the second catalytic layer is 0.5 to 5 μm, preferably 1 to 2 μm.

[0057] In the embodiment of the present application, the second catalytic layer further includes a catalyst;

[0058] The second material further includes a catalyst; and the content of the ionomer resin in the second solid material is greater than the content of the ionomer resin in the first solid material.

[0059] Specifically, the second catalyst layer also includes a catalyst, so that the second catalyst layer becomes a redox reaction site, effectively avoiding the second catalyst layer being composed of only ionomers and increasing the proton conduction path, and at the same time, the content of the ionomer resin in the second solid material is greater than the content of the ionomer resin in the first solid material to ensure the surface compatibility of the second catalyst layer and the proton exchange membrane. The ratio of the catalyst to the ionomer resin is in the range of 2 to 30, preferably 5 to 15, according to the I / C range, the catalyst is selected from mesoporous or spherical carbon type, and the ionomer resin can be selected from perfluorosulfonic acid resin, wherein I / C refers to the mass ratio of the ionomer resin to the carbon carrier in the catalyst.

[0060] In an embodiment of the present application, the second catalytic layer also includes carbon material; the second material also includes the carbon material; the carbon material includes one or more combinations of carbon nanotubes, carbon fibers, and graphene.

[0061] Specifically, the second catalytic layer also includes carbon material, which can increase the porosity inside the second catalytic layer and avoid the fuel transmission problem caused by the ionomer resin of the second catalytic layer completely covering the catalyst inside the second catalytic layer, affecting the redox reaction in the catalytic site.

[0062] In the embodiment of the present application, the solid content of the second material is lower than the solid content of the first material; the solid content represents the mass percentage of the solid material in the material; the solid content of the second material is 1% to 25%; the thickness of the second catalytic layer is less than the thickness of the first catalytic layer.

[0063] Specifically, by making the solid content of the second material lower than the solid content of the first material, it is easier to obtain a second catalytic layer that is thinner than the first catalytic layer. In the present application, the first catalytic layer is still the catalytic layer that plays the main catalytic role. Adding a second catalytic layer that is thinner than the first catalytic layer can reduce the interface impedance between the catalytic layer and the proton exchange membrane, thereby improving the catalytic performance of the catalyst coating proton membrane.

[0064] In the embodiment of the present application, the second solvent includes water and an organic solvent; the mass ratio of water to the mass ratio of the organic solvent is 0.1 to 10.

[0065] Specifically, a second solvent is provided in a mass ratio of water to organic solvent between 0.1 and 10 to obtain a second catalytic layer with a better microporous structure, and the organic solvent includes one or more solvent combinations selected from ethanol, n-propanol, isopropanol, N-methylpyrrolidone (NMP), acetonitrile, etc.

[0066] The embodiments of the present application also provide a catalyst-coated proton membrane, including a catalyst-coated proton membrane prepared by any one of the preparation methods provided in the embodiments of the present application.

[0067] Specifically, the embodiment of the present application provides a transfer matrix and a proton exchange membrane; forms a first catalytic layer on the transfer matrix, the first catalytic layer includes an ionomer resin and a catalyst, specifically including: providing a first material, the first material includes a first solid material and a first solvent; the first solid material includes an ionomer resin and a catalyst; applying the first material on the transfer matrix to form a first catalytic layer on the transfer matrix; forming a second catalytic layer on the first catalytic layer, the second catalytic layer includes an ionomer resin, specifically including: providing a second material, the second material includes a second solid material and a second solvent; the second solid material includes an ionomer resin; applying the second material on the first catalytic layer to form a second catalytic layer on the first catalytic layer; wherein the second catalytic layer also includes a catalyst, the second material also includes a catalyst, and the content of the ionomer resin in the second solid material is greater than the ionomer resin in the first solid material. The second catalytic layer also includes a carbon material, the second material also includes a carbon material, the carbon material includes one or more combinations of carbon nanotubes, carbon fibers, and graphene, the solid content of the second material is lower than the solid content of the first material, the solid content characterizes the mass percentage of the solid material in the material, the solid content of the second material is 1% to 25%, the thickness of the second catalytic layer is less than the thickness of the first catalytic layer, the second solvent includes water and an organic solvent; the mass ratio of water to the mass ratio of the organic solvent is 0.1 to 10; the first catalytic layer and the second catalytic layer on the transfer substrate are transferred to the proton exchange membrane through a transfer process, so that the second catalytic layer is located on the proton exchange membrane and the first catalytic layer is located on the second catalytic layer, to obtain a catalyst coated proton membrane, wherein the process conditions of the transfer process include: a temperature of 120 to 170° C., a transfer pressure of 2 to 2.5 MPa, and a transfer time of 2 to 3 min.

[0068] The embodiments of the present application also provide a membrane electrode, comprising any catalyst-coated proton membrane provided in the embodiments of the present application.

[0069] A membrane electrode provided in an embodiment of the present application includes any catalyst-coated proton membrane provided in an embodiment of the present application. The present invention has no special requirements for the preparation method of other parts of the membrane electrode except the catalyst-coated proton membrane, and the conventional membrane electrode preparation method in the art can be adopted. The specific preparation process is well known in the membrane electrode field and will not be elaborated here.

[0070] The embodiment of the present application also provides a fuel cell, including a membrane electrode provided by the embodiment of the present application.

[0071] A fuel cell provided in an embodiment of the present application includes a membrane electrode provided in an embodiment of the present application. The present invention has no special requirements for the fuel cell preparation method, and a conventional fuel cell preparation method in the art can be adopted. The specific preparation process is well known in the fuel cell field and will not be described in detail here.

[0072] The present invention will be described in detail below through examples.

[0073] First, a proton exchange membrane and a polytetrafluoroethylene (PTFE) transfer membrane are provided; the materials include: a Pt / C catalyst (Pt loading is 50wt%, carbon loading is 50wt%), a perfluorosulfonic acid resin solution (perfluorosulfonic acid resin is referred to as PFSA, and its solid content is 20%), ultrapure water, n-propanol, and a carbon material.

[0074] By using slit coating, scraping, spraying and other processes, the first and second catalytic layers with uniform platinum (Pt) loading and consistent thickness in the catalyst are obtained on the transfer substrate, and then the CCM is obtained by transfer process. Finally, the CCM is encapsulated to obtain the membrane electrode, in which the Pt loading of the cathode catalyst layer of the membrane electrode can be 0.3mg / cm 2 The standard for completion of transfer is complete transfer without any residue on the transfer substrate.

[0075] Example 1

[0076] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0077] Preparation of the first catalytic layer:

[0078] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0079] Preparation of the second catalytic layer:

[0080] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 7.45 g of ultrapure water, 74.5 g of n-propanol and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was performed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spray coating method was adopted, the coating temperature was 90°C, and the spray coating parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 125°C, a transfer pressure of 2 MPa, and a transfer time of 2 min.

[0081] The conventional method was used to test the electrochemical performance of the membrane electrode assembly (MEA) after packaging. The test conditions were 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80 °C for battery temperature. The test results were: 2 Under the condition of electric density, the voltage is 0.590V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.001Ω.

[0082] Example 2

[0083] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0084] Preparation of the first catalytic layer:

[0085] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0086] Preparation of the second catalytic layer:

[0087] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 12.56 g of ultrapure water, 125.65 g of n-propanol and 12.5 g of perfluorosulfonic acid resin solution according to I / C=10 were weighed respectively, and slurry dispersion was performed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spraying method was adopted, and the coating temperature was 90°C. The spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 120°C, a transfer pressure of 2 MPa, and a transfer time of 2 min.

[0088] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.562V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.001Ω.

[0089] Example 3

[0090] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0091] Preparation of the first catalytic layer:

[0092] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0093] Preparation of the second catalytic layer:

[0094] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 22.79 g of ultrapure water, 227.9 g of n-propanol and 25 g of perfluorosulfonic acid resin solution according to I / C=20 were weighed respectively, and slurry was dispersed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spraying method was adopted, the coating temperature was 90°C, and the spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 120°C, a transfer pressure of 2 MPa, and a transfer time of 2 min.

[0095] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.515V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.001Ω.

[0096] Example 4

[0097] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0098] Preparation of the first catalytic layer:

[0099] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0100] Preparation of the second catalytic layer:

[0101] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 4.38 g of ultrapure water, 43.8 g of n-propanol and 2.5 g of perfluorosulfonic acid resin solution according to I / C=2 were weighed respectively, and slurry was dispersed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spraying method was adopted, the coating temperature was 90°C, and the spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0102] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.554V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0013Ω.

[0103] Example 5

[0104] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0105] Preparation of the first catalytic layer:

[0106] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0107] Preparation of the second catalytic layer:

[0108] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 15.52 g of ultrapure water, 155.2 g of n-propanol and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was carried out by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 1%; a spraying method was adopted, the coating temperature was 90°C, and the spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0109] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.583V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0011Ω.

[0110] Example 6

[0111] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0112] Preparation of the first catalytic layer:

[0113] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0114] Preparation of the second catalytic layer:

[0115] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 0.03 g of ultrapure water, 0.3 g of n-propanol and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was carried out by ball milling for 24 hours to obtain a second material with uniform particle size distribution and a solid content of 25%; a spraying method was adopted, the coating temperature was 90°C, and the spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0116] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.579V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0012Ω.

[0117] Example 7

[0118] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0119] Preparation of the first catalytic layer:

[0120] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0121] Preparation of the second catalytic layer:

[0122] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 74.52 g of ultrapure water, 7.45 g of n-propanol and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry was dispersed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spraying method was adopted, the coating temperature was 90°C, and the spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0123] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.567V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0011Ω.

[0124] Example 8

[0125] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0126] Preparation of the first catalytic layer:

[0127] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0128] Preparation of the second catalytic layer:

[0129] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 33 g of ultrapure water, 330.2 g of n-propanol and 37.5 g of perfluorosulfonic acid resin solution according to I / C=30 were weighed respectively, and slurry dispersion was carried out by ball milling for 24 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spraying method was adopted, the coating temperature was 90°C, and the spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0130] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.514V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.001Ω.

[0131] Example 9

[0132] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0133] Preparation of the first catalytic layer:

[0134] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0135] Preparation of the second catalytic layer:

[0136] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 17.57 g of ultrapure water, 175.68 g of n-propanol and 18.75 g of perfluorosulfonic acid resin solution according to I / C=15 were weighed respectively, and slurry dispersion was performed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spraying method was adopted, the coating temperature was 90°C, and the spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0137] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.568V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0009Ω.

[0138] Example 10

[0139] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0140] Preparation of the first catalytic layer:

[0141] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0142] Preparation of the second catalytic layer:

[0143] 0.5 g of Pt / C catalyst, 0.0005 g of carbon fiber, 7.34 g of ultrapure water, 73.43 g of n-propanol and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was performed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spray coating method was adopted, the coating temperature was 90°C, and the spray coating parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0144] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.582V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.001Ω.

[0145] Embodiment 11

[0146] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0147] Preparation of the first catalytic layer:

[0148] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0149] Preparation of the second catalytic layer:

[0150] 0.5 g of Pt / C catalyst, 0.5 g of carbon fiber, 9.57 g of ultrapure water, 95.68 g of n-propanol and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was carried out by ball milling for 24 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spray coating method was adopted, the coating temperature was 90°C, and the spray coating parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 170°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0151] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.534V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.001Ω.

[0152] Example 12

[0153] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0154] Preparation of the first catalytic layer:

[0155] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0156] Preparation of the second catalytic layer:

[0157] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 7.45 g of ultrapure water, 74.52 g of acetonitrile and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was performed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spray coating method was adopted, the coating temperature was 90°C, and the spray coating parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0158] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.545V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0011Ω.

[0159] Example 13

[0160] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0161] Preparation of the first catalytic layer:

[0162] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0163] Preparation of the second catalytic layer:

[0164] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 7.45 g of ultrapure water, 74.52 g of NMP and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was performed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spray coating method was adopted, the coating temperature was 90°C, and the spray coating parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0165] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.538V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0011Ω.

[0166] Embodiment 14

[0167] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0168] Preparation of the first catalytic layer:

[0169] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0170] Preparation of the second catalytic layer:

[0171] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 7.45 g of ultrapure water, 37.26 g of acetonitrile and 37.26 g of NMP, and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was performed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spray coating method was adopted, the coating temperature was 90°C, and the spray coating parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0172] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.546V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0011Ω.

[0173] Embodiment 15

[0174] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0175] Preparation of the first catalytic layer:

[0176] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0177] Preparation of the second catalytic layer:

[0178] 0.5 g of Pt / C catalyst, 0.025 g of carbon nanotubes, 7.45 g of ultrapure water, 74.5 g of n-propanol and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was performed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spray coating method was adopted, the coating temperature was 90°C, and the spray coating parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 125°C, a transfer pressure of 2 MPa, and a transfer time of 2 min.

[0179] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.583V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.001Ω.

[0180] Example 16

[0181] This embodiment is used to illustrate a catalyst-coated proton membrane and a preparation method thereof, a membrane electrode and a fuel cell of the present invention.

[0182] Preparation of the first catalytic layer:

[0183] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0184] Preparation of the second catalytic layer:

[0185] 0.5 g of Pt / C catalyst, 0.025 g of graphene, 7.45 g of ultrapure water, 74.5 g of n-propanol and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was performed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spray coating method was adopted, the coating temperature was 90°C, and the spray coating parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 125°C, a transfer pressure of 2 MPa, and a transfer time of 2 min.

[0186] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.588V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.001Ω.

[0187] Comparative Example 1

[0188] Catalytic layer preparation:

[0189] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and coated on the transfer substrate by slit coating to form a catalytic layer on the transfer substrate; flat plate transfer was selected through the transfer process, and the catalytic layer was completely transferred to the surface of the proton exchange membrane, wherein the conditions of the transfer process included: temperature of 155°C, transfer pressure of 3 MPa, and transfer time of 5 min.

[0190] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.506V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0014Ω.

[0191] Comparative Example 2

[0192] Preparation of the first catalytic layer:

[0193] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0194] Preparation of the second catalytic layer:

[0195] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 7.45 g of ultrapure water, 74.5 g of n-propanol and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was performed by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spraying method was adopted, the coating temperature was 90°C, and the spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 100°C, a transfer pressure of 3Mpa, and the transfer could not be completed.

[0196] Comparative Example 3

[0197] Preparation of the first catalytic layer:

[0198] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0199] Preparation of the second catalytic layer:

[0200] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 7.45 g of ultrapure water, 74.5 g of n-propanol and 6.25 g of perfluorosulfonic acid resin solution according to I / C=5 were weighed respectively, and slurry dispersion was carried out by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spraying method was adopted, the coating temperature was 90°C, and the spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 180°C, a transfer pressure of 2 MPa, and a transfer time of 2 min.

[0201] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.516V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0013Ω.

[0202] Comparative Example 4

[0203] Preparation of the first catalytic layer:

[0204] 2 g of Pt / C catalyst, 5 g of PFSA resin solution, 20.25 g of ultrapure water, and 6.75 g of n-propanol were weighed and mixed evenly as the first material, and then coated on the transfer substrate by slit coating to form a first catalytic layer on the transfer substrate.

[0205] Preparation of the second catalytic layer:

[0206] 0.5 g of Pt / C catalyst, 0.025 g of carbon fiber, 2.85 g of ultrapure water, 28.5 g of n-propanol and 0.625 g of perfluorosulfonic acid resin solution according to I / C=0.5 were weighed respectively, and slurry dispersion was carried out by ball milling for 12 hours to obtain a second material with uniform particle size distribution and a solid content of 2%; a spraying method was adopted, the coating temperature was 90°C, and the spraying parameters were adjusted to control the second catalytic layer with a thickness of 1.5 μm; a flat plate transfer was selected through a transfer process to completely transfer the above-mentioned first catalytic layer and the second catalytic layer to a proton exchange membrane, so that the second catalytic layer was located on the proton exchange membrane and the first catalytic layer was located on the second catalytic layer, to obtain a catalyst-coated proton membrane; wherein the conditions of the transfer process include: a temperature of 145°C, a transfer pressure of 2.5 MPa, and a transfer time of 3 min.

[0207] After MEA packaging is completed, the electrochemical performance test is carried out using conventional methods. The test conditions are 100 RH% for cathode and anode, 2:3 for cathode and anode stoichiometry, 170 / 150 kPa for cathode and anode back pressure, and 80°C for battery temperature. The test results are: 2 Under the condition of electric density, the voltage is 0.502V; at 1.6A / cm 2 Under electrical tightness conditions, the ohmic resistance is 0.0016Ω.

[0208] Taking Examples 1-4 and Comparative Example 1 as examples, the transfer process conditions of Comparative Example 1 are the most stringent, with a transfer temperature of up to 155° C., a transfer pressure of 3 MPa, and a maximum transfer time of 5 min. Figure 2 Comparison of polarization curves of voltage and resistance of different membrane electrodes, please refer to Figure 2,about Figure 2 In the case where V represents voltage and R represents resistance, i.e., internal resistance, the electrochemical performance test found that the internal resistance value of comparative example 1 is the largest, indicating that the interface impedance between the proton membrane and the catalyst layer caused by the transfer process is relatively large, which also leads to its lowest performance. When the second catalyst layer I / C=5, the temperature, transfer pressure and transfer time of the transfer process are effectively reduced. The compatibility of the second catalyst layer with the proton exchange membrane reduces the interface impedance, and its internal resistance is correspondingly reduced. In addition, the control of the catalyst content effectively improves the performance of the battery itself, and ultimately improves the electrochemical performance of the membrane electrode. It is found from Examples 2 and 3 that when I / C is increased to 10 and 20, the transfer condition is only reduced by 5°C in temperature, but the corresponding catalyst and carbon fiber content are reduced, resulting in a significant reduction in its electrocatalytic ability, especially when I / C=20 in Example 3, which is equivalent to the second catalyst layer of the pure ionomer resin layer covering, reducing fuel transmission; when it is reduced to I / C=2, the catalyst content increases, the ionomer resin content decreases, and the interface internal resistance increases again, resulting in reduced electrochemical performance.

[0209] It can be known from the above technical scheme of the embodiment of the present invention that the present invention discloses a method for preparing a catalyst-coated proton membrane, providing a transfer substrate and a proton exchange membrane, forming a first catalyst layer including an ionomer resin and a catalyst on the transfer substrate; forming a second catalyst layer including an ionomer resin on the first catalyst layer; transferring the first catalyst layer and the second catalyst layer on the transfer substrate to the proton exchange membrane through a transfer process, so that the second catalyst layer is located on the proton exchange membrane and the first catalyst layer is located on the second catalyst layer, thereby obtaining a catalyst-coated proton membrane. The present invention provides two catalyst layers, adds a second catalyst layer between the first catalyst layer and the proton exchange membrane, and the second catalyst layer is an ionomer resin layer, thereby improving the compatibility of the catalyst layer with the surface of the proton exchange membrane, reducing the interface impedance between the catalyst layer and the proton exchange membrane, and improving the proton conduction efficiency, thereby improving the performance of the membrane electrode based on the catalyst-coated proton membrane.

[0210] The above description has fully disclosed the specific embodiments of the present invention. It should be pointed out that any changes made by those skilled in the art to the specific embodiments of the present invention do not deviate from the scope of the claims of the present invention. Accordingly, the scope of the claims of the present invention is not limited to the above specific embodiments.

Claims

1. A method for preparing a catalyst-coated proton membrane, characterized in that: The method comprises: Providing transfer matrix and proton exchange membrane; forming a first catalyst layer on the transfer substrate; the first catalyst layer comprises an ionomer resin and a catalyst; forming a second catalytic layer on the first catalytic layer; the second catalytic layer comprises an ionomer resin; The first catalytic layer and the second catalytic layer on the transfer substrate are transferred to the proton exchange membrane through a transfer process, so that the second catalytic layer is located on the proton exchange membrane and the first catalytic layer is located on the second catalytic layer, thereby obtaining a catalyst-coated proton membrane.

2. A method according to claim 1, characterized in that The process conditions of the transfer process include: The temperature is 120-170°C; The transfer pressure is 2-2.5Mpa; The transfer time is 2 to 3 minutes.

3. A method according to claim 1, characterized in that The forming of a first catalytic layer on the transfer substrate comprises: Providing a first material; the first material comprises a first solid material and a first solvent; the first solid material comprises an ionomer resin and a catalyst; Applying the first material on the transfer substrate to form a first catalytic layer on the transfer substrate; The forming of a second catalytic layer on the first catalytic layer comprises: Providing a second material; the second material comprises a second solid material and a second solvent; the second solid material comprises an ionomer resin; The second material is applied on the first catalytic layer to form a second catalytic layer on the first catalytic layer.

4. A method according to claim 3, characterized in that The second catalytic layer also includes a catalyst; The second material further comprises a catalyst; and the content of the ionomer resin in the second solid material is greater than the content of the ionomer resin in the first solid material.

5. A method according to claim 4, characterized in that The second catalytic layer also includes a carbon material; The second material also includes the carbon material; The carbon material includes one or more combinations of carbon nanotubes, carbon fibers, and graphene.

6. A method according to claim 5, characterized in that The solid content of the second material is lower than the solid content of the first material; the solid content represents the mass percentage of the solid material in the material; The solid content of the second material is 1% to 25%; The thickness of the second catalytic layer is smaller than the thickness of the first catalytic layer.

7. A method according to claim 3, characterized in that: The second solvent includes water and an organic solvent; the mass ratio of the water to the organic solvent is 0.1-10.

8. A catalyst-coated proton membrane, comprising any catalyst-coated proton membrane prepared by the method according to any one of claims 1 to 7.

9. A membrane electrode, comprising the catalyst-coated proton membrane according to claim 8.

10. A fuel cell comprising the membrane electrode according to claim 9.